Jihād, Gender, and Religious Minorities in the Siyar Literature: the Diachronic View - Afsaruddin, Asma (Studia Islamica, 2020)
Siyar in Islamic law refers to the law of nations or international law. This study focuses on five siyar works composed between the 2nd/8th and 7th/13th centuries in order to compare and analyze their content diachronically in connection with two specific topics. The first topic is concerned with changing juridical conceptualizations of the role of the combative or military jihād in the Muslim polity's relations with non-Muslim ones during this period. The second has to do with the evolution of siyar rules governing the treatment of non-Muslim and female participants in the military jihād, especially in the matter of the division of spoils. Four of these works represent the four major Sunnī madhāhib while the fifth is an early work predating the formation of these schools of law. Comparison of the content of these works allows us to draw certain conclusions about the nature and purview of the military jihād, as progressively articulated by jurists during the period under discussion. One of the major conclusions to be drawn from this study is that the combative jihād became an exclusively masculine and Muslim activity and effectively excluded women and non-Muslims from participation in it after the 2nd/8th century.